DARI SIKAP PEDULI SOSIAL REMAJA MENUJU PEMBIASAAN INFAK DAN SEDEKAH: STUDI FILANTROPI SOSIAL PADA FORUM KOMUNIKASI REMAJA MASJID LEBAK, RANGKASBITUNG - Euis Ismayati Yuniar (Department of Islamic Community Development, Faculty of Da'wah, State Islamic University (UIN) of Sultan Maulana Hasanuddin Banten, 2021)
The objectives to be achieved in this study are to: analyze the influence between the habit of infaq and alms together towards the development of adolescent social care attitudes at the Lebak Rangkasbitung Mosque Youth Communication Forum. This quantitative research uses the Pre Experimental Design method, with the One-Shot Case Study approach model, which is an approach model that uses one time data collection at a